The vulnerabilities of the gas supply system of the Republic of Moldova in the context of its energetic security - Iulian VIȚĂ; Cristina Elena NICOLESCU (Theoretical and Applied Economics, 2017)

(untitled)
In the context of the current “volatile” equation of energy resources at the world, regional and local level, impacted by the decline of the “sovereign oil era” and by the shifting of the weight center on the use of gas, renewable resources and increased efficiency – considered a new type of energy resource, the topic of energy security gains enhanced weight in the governments’ working agenda, in particular for the states currently in a situation of major dependency on the energy resources of other countries, as is the case of the Republic of Moldova, almost completely energetically dependent on the import of natural gases from Russia. The paper at hand aims to emphasize the energy security vulnerabilities of the Republic of Moldova, state which, following the signing of the EU Association Agreement and the entering into effect of this document in 2016 should become, as the EU member-states, energy security supplier for the EU. The methodology used is preponderantly qualitative and based on the analysis of official documents, key information, case studies, the analysis performed in this paper providing important information for the policy makers’ agenda for planning and management purposes and for energy sector in the Republic of Moldova, in considering its foreign policy-specific national interests.